Cognitive Analysis of Madness in Qays ibn al-Moullawwāh’s Poem “When Will This Heart Find Rest” - Darwish, Layla (Universitas Mulawarman, 2025)
This study analyzes the poetry of Qays ibn al-Mulawwaḥ to reconsider the notion of madness traditionally attributed to him. Rather than a psychological disorder or a reflection of biographical narratives, madness is shown to function as a cognitive-emotional structure produced through poetic language. Drawing on conceptual metaphor theory, force dynamics, and cognitive grammar, the study demonstrates how imagery, grammatical organization, and embodied patterns construct experiences of longing, alienation, and emotional turbulence, revealing madness as a linguistically structured mode of emotional and cognitive experience in early Arabic poetry.